(untitled) (Medical Forum Monthly, 2024)
Objective: General anesthesia is most frequently used for lumbar disc surgery despite the evidence that spinal anesthesia is as safe and may offer some additional advantages. The purpose of this study was to compare the intraoperative parameters and postoperative outcome after spinal and general anesthesia in demographically well matched patients undergoing elective lumbar Decompressive surgery. Study Design: Prospective randomized controlled study Place and Duration of Study: This study was carried out at DHQ Hospital Mirpur AJK from January 2007 and May 2010. Materials and Methods: In this randomized controlled study we analyzed the outcome obtained in 44 patients in whom either spinal or general anesthesia was induced for lumbar disc surgery. The variables recorded were anesthesia related class, surgical diagnosis, disc levels operated and pre,peri and postoperative measurements of variables like BP, and heart rate. All aspects of surgery, recovery, post anesthesia care and pain management were same irrespective of anesthetic type The narcotic and antiemetic requirement and length of stay in the hospital and incidence of urinary retention were also recorded in the post operative course. Results: Demographically both groups were well matched. Anesthesia time was longer in patients receiving GA with increased heart rate and MABP perioperatively. There was more nausea and greater requirements for antiemetic and analgesics in patients receiving GA(p value<0.05). Perioperative heart rate and MABP was on normal side and there was no urinary retention in patients who received spinal anesthesia. Conclusion: Spinal anesthesia was a safe and effective as GA for patients undergoing lumbar Decompressive surgery. Spinal anesthesia had added advantages of short anesthesia duration, decreased antiemetic and analgesic requirements. Abbreviations: GA general anesthesia, HR heart rate, I/V intravenous, MAP mean arterial pressure, PACU post anesthesia care unit, RCT randomized controlled trial, SA spinal anesthesia